Reinterpretasi Tanggung Jawab Sosial Perusahaan Adat dalam Konstruksi Hukum CSR Labda Pencingkreman Desa Berbasis Tri Hita Karana - Satrya Wibawa, Gede Yoga (Jurnal Penelitian Agama Hindu, 2025)
Corporate Social Responsibility (CSR) models in national legal frameworks are often procedural and market-driven, overlooking community-based practices rooted in local values and customary institutions. This study aims to reconstruct an indigenous CSR model by examining the Labda Pencingkreman Desa (LPD), a village-owned financial institution in Bali, through the philosophical framework of Tri Hita Karana. The research adopts a qualitative interpretive approach, combining legal ethnography and normative legal analysis. Data were collected through in-depth interviews, participatory observation, and document review in Selat Nyuhan Customary Village, Bangli. Findings indicate that CSR in the LPD context is not philanthropic or voluntary, but a collective social and spiritual obligation embedded in awig-awig (customary law) and enacted through village assemblies (paruman). CSR is operationalized across three dimensions: religious support (parhyangan), social welfare programs (pawongan), and environmental conservation (palemahan), all aligned with the values of Tri Hita Karana. The study concludes that customary institutions can serve as legitimate actors in implementing culturally grounded CSR. It recommends the development of a hybrid social accountability model that bridges customary norms and formal governance mechanisms to support sustainable development.